Comparison of the Competitiveness of Chinese and Korean Cultural Industries Based on the Perspective of New Institutional Economics - Chen, Xiaoyu (International Journal of Global Economics and Management, 2024)
Based on the perspective of new institutional economics, this paper compares the competitiveness of the cultural industries in China and South Korea, and analyses the similarities and differences between the two countries in terms of the institutional environment, market structure and business cases. By sorting out the theoretical framework of new institutional economics, it explores the influence of factors such as property rights system, transaction costs and cultural industry efficiency on the development of cultural industry. China's cultural industry has advantages in terms of policy support and market scale, but the problems of insufficient intellectual property protection and imperfect market mechanism still restrict its international competitiveness. In contrast, South Korea's cultural industry is known for its mature market mechanism, strong content creation ability and effective intellectual property protection, which has successfully promoted the global spread of the "Korean Wave" culture. Through case studies of typical enterprises such as Tencent and YG Entertainment, the differences in competitiveness between the two countries' cultural enterprises in the international market are revealed. Finally, puts forward suggestions to optimise the institutional environment, strengthen international cooperation and promote cultural innovation, so as to promote the sustainable development of the cultural industries in China and South Korea. The research in this paper provides theoretical basis and empirical support for an in-depth understanding of the development mode and international competitiveness of Chinese and Korean cultural industries.